Exploring the potential of gold(iii) cyclometallated compounds as cytotoxic agents: variations on the C^N theme1. Issue 26 (14th July 2015) - Bertrand, B.; Spreckelmeyer, S.; Bodio, E.; Cocco, F.; Picquet, M.; Richard, P.; Le Gendre, P.; Orvig, C.; Cinellu, M. A.; Casini, A.
<x xml:space="preserve">Abstract</x> New (C^N) cyclometallated Au(iii) complexes with cytotoxic properties shown to be potent inhibitors of the zinc finger protein PARP-1.